Probiotic Fermented Sausages: Myth or Reality?. (2015) - Jofré, Anna; Aymerich, Teresa; Garriga, Margarita
Abstract: Experts view the development of functional foods as an opportunity for innovation for the meat industry in line with consumers' concerns on food nutrition, well being and food safety. The main microbiota of fermented sausages consists of lactobacilli, which suggests that properly characterized strains could be selected as starter cultures. The selection of strains from human origin was considered in order to promote their survival in the host. Lactobacillus rhamnosus CTC1679 dominated during the ripening process and temporarily colonized the gastrointestinal tract of healthy volunteers, confirming that this strain could be delivered as a potential probiotic in fermented sausages.